2020
DOI: 10.1002/nau.24424
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone inhibits stress‐induced bladder hyperalgesia and alters cerebral micturition and nociceptive circuits in the rat: A multidisciplinary approach to the study of urologic chronic pelvic pain syndrome research network study

Abstract: Aims Emotional stress plays a role in the exacerbation and development of interstitial cystitis/bladder pain syndrome (IC/BPS). Given the significant overlap of brain circuits involved in stress, anxiety, and micturition, and the documented role of glutamate in their regulation, we examined the effects of an increase in glutamate transport on central amplification of stress‐induced bladder hyperalgesia, a core feature of IC/BPS. Methods Wistar‐Kyoto rats were exposed to water avoidance stress (WAS, 1 hour/day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 129 publications
(148 reference statements)
0
17
0
Order By: Relevance
“…We have shown that XST elevated CBF in both APP/PS1 and WT mice ( Huang et al, 2018 ), and thus elevated CBF could drive the improved LV structure/function. Since ceftriaxone (Cef) injection reliably increases CBF ( Kortela et al, 2017 ; Holschneider et al, 2020 ), we first confirmed this in the APP/PS1 mice using two-photon linescan imaging ( Huang et al, 2018 ). We have focused on small BVs (diameters 7–15 μm) due to their reported alteration in AD ( Ahn et al, 2018 ; Bracko et al, 2019 ) and used medium-sized vessels as control (diameters 40–60 μm).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…We have shown that XST elevated CBF in both APP/PS1 and WT mice ( Huang et al, 2018 ), and thus elevated CBF could drive the improved LV structure/function. Since ceftriaxone (Cef) injection reliably increases CBF ( Kortela et al, 2017 ; Holschneider et al, 2020 ), we first confirmed this in the APP/PS1 mice using two-photon linescan imaging ( Huang et al, 2018 ). We have focused on small BVs (diameters 7–15 μm) due to their reported alteration in AD ( Ahn et al, 2018 ; Bracko et al, 2019 ) and used medium-sized vessels as control (diameters 40–60 μm).…”
Section: Resultsmentioning
confidence: 70%
“…One major in vivo effect of XST is elevated CBF in both AD and WT mice ( Huang et al, 2018 ), and this efficacy has been the main rationale for XST’s medical use in China ( Du et al, 2015 ; Huang et al, 2018 ). Interestingly, Cef injection did not modulate LV structure and function albeit it significantly enhances CBF ( Holschneider et al, 2020 ). Hence, despite the numerous and complex interactions between CBF and LVs ( Kisler et al, 2017 ), directly enhancing CBF may not affect LVs, suggesting segregation of these two important fluid exchange systems in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…1 Rats exposed to chronic WAS showed bladder hyperalgesia and decreased threshold of micturition, in addition to increased micturition frequency. 19,20,[24][25][26][27][28][29][30] These chronic WAS-induced changes, urinary function and nociception in the bladder of rats are similar to clinical features observed in patients with IC/ BPS; 31,32 therefore, this animal model has been widely used to investigate the pathogenesis of IC/BPS. In the bladder, exposure to chronic WAS in rats induced increased subepithelial infiltration of mast cells 1,26 and mitochondrial dysfunction in the urothelium.…”
Section: Water Avoidance Stressmentioning
confidence: 56%
“…26,33 Furthermore, chronic exposure to WAS in rats enhanced activity of glutamatergic nerves in the L6-S2 lumbosacral region due to downregulation of Glt1, which is responsible for glutamate clearance in the synaptic cleft to terminate glutamatergic neurotransmission, 34 and pretreatment with ceftriaxone, an activator of Glt1, improved the WAS-induced bladder hyperalgesia and increased micturition frequency. 19,30 Therefore, pharmacological strategies targeting the sympathetic nervous system and the central glutamatergic nervous system might alleviate psychological stress (WAS)-induced development of LUTDs.…”
Section: Water Avoidance Stressmentioning
confidence: 99%
“…Pregabalin treatment decreased hyperalgesia and reduced inflammation by reducing proinflammatory cytokine production and inhibiting NF-κB activation [ 66 ], while systemic administration of gabapentin reduced cystitis-related pain and frequency of voiding [ 67 ]. Ceftriaxone, a β-lactam antibiotic, diminished visceral hypersensitivity in stress-induced IC rats [ 68 ], while neurokinin-1 receptor antagonist aprepitant, used to treat nausea, relieved pelvic pain, urinary symptoms, and bladder inflammation in mice with experimental autoimmune cystitis [ 69 ]. Given the substantial costs and time of new drug discovery and development, drug repurposing could represent an attractive option to treat IC/BPS patients, according to the promising results of preclinical research.…”
Section: Resultsmentioning
confidence: 99%